Understanding language teaching : from method to post-method - Kumaravadivelu, B., 1948- (ESL and applied linguistics professional series., 2006)
Drawing from seminal, foundational texts and from critical commentaries made by various scholars, the author examines the profession's transition from method to postmethod and, in the process, elucidates the relationship between theory, research, and practice. This book is intended for teacher educators, practicing teachers and graduate students.